1992
DOI: 10.1002/app.1992.070441109
|View full text |Cite
|
Sign up to set email alerts
|

Maleation of linear low‐density polyethylene by reactive processing

Abstract: SYNOPSISThe reaction of maleic anhydride (MAH) with molten 2 MI poly( ethylene-co-butene-1) (LLDPE) a t 160°C in the presence of peroxyesters ( tllz < 10 s ) as catalysts resulted in the formation of a mixture of cross-linked and trichlorobenzene-soluble LLDPE-g-MAH.The soluble fraction constituted more than 50% of the mixture and had an MI of 0.0 and an MAH content ranging from 0.3 to 1.8 wt %. The presence of tri (nonylphenyl) phosphite (TNPP) in the LLDPE-MAH-t-butyl peroctoate ( tBPO) reaction at 160°C inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 8 publications
1
60
1
1
Order By: Relevance
“…In recent years, there has been considerable progress in the modi¯cation of polyole¯ns by the methods of graft copolymerization with polar monomers [1][2][3][4]. The solid state graft copolymerization of PE and PP with maleic anhydride (MAH), maleic acid (MA) or its salts is a promising method capable of retaining the mechanical properties of the initial polymers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been considerable progress in the modi¯cation of polyole¯ns by the methods of graft copolymerization with polar monomers [1][2][3][4]. The solid state graft copolymerization of PE and PP with maleic anhydride (MAH), maleic acid (MA) or its salts is a promising method capable of retaining the mechanical properties of the initial polymers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,19,20 The higher the [peroxide]/[MAH] ratio, the higher the MAH excited species concentration and, consequently, the higher the grafting and crosslinking degree obtained. The highest grafting degree was obtained at 150°C.…”
Section: Resultsmentioning
confidence: 97%
“…Then, the GD of LLDPE-g-MAH was chemically titrated by potassium hydroxide (KOH) solution in isopropyl alcohol as reported in the literature [8,9], and was calculated by the following equation:…”
Section: Characterizationmentioning
confidence: 99%
“…Many efforts have been made to enhance the grafting degree (GD) and reduce the gel content (GC). Gaylord and coworkers [7][8][9] proposed that the addition of nitrogen-, phosphorous-, and sulfur-containing organic electron donors could prevent the crosslinking of PE and homopolymerization of MAH. Yao et al [10] also found that p-benzoquinone, triphenyl phosphate, and tetrachlomethane are good inhibitors for crosslinking of linear low-density polyethylene (LLDPE) during free radical graft polymerization.…”
Section: Introductionmentioning
confidence: 99%